(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2020)
The aim of Education for the 21st Century is to enable every person to attain all-round development in the domains of ethics, intellect, physique, social skills and aesthetics according to his/her attributes so as to contribute to the future well-being of the nation and the world as a whole. The aim of the study was to assess the provision and maintenance of educational facilities in Ekiti State, Nigeria with a focus on the Ekiti-South West LGA and Community-Based Development Associations in the study area. This study adopted the survey research method and used three different sets of a questionnaire to collect research data from the authority of the Ekiti South-West LG Council officials, Community Development Unit of the LG Council and the 61 (CBDAs) officials were available in the study area. The findings among others revealed that majority of the secondary schools were privately-owned, while the primary and nursery/primary schools were Community-owned. However, the present monthly allocation from Federal Government to LGCs is grossly inadequate, and it is not enough to embark on provision and maintenance of educational facilities. Given the findings, there were need to improve the schools through additional appropriation and maintenance of the existing schools; finally, the governments and other stakeholders should inculcate good maintenance culture on our educational facilities for effective management with the intention of promoting high-quality education for the well-being of the nation.